La dinamización del eje férreo de Neiva inspirada en los mitos huilenses y su identidad cultural. - Garcia Blasquez, Juan Manuel; Espinosa Ascencio, Nicole Fernanda (Universidad Antonio Nariño, 2024)
The railways are a real estate that with the modernization of cities and the growth of the urban footprint have been buried; In the case of the city of Neiva-Huila, it still preserves the structures of its cellars, parts of the rails that once crossed the land and the railway station, forming the old railway shaft. The municipality declared the station as immovable architectural heritage for its historical role and the railway corridor as priority tourism development area according to the POT, however, the space is currently in decline, being vandalized and invaded by private and public entities which causes the hindrance of connectivity in this axis of the city, losing the viability of the pedestrian and disappearing the history and cultural importance of its railway system. Previously, urban projects have been proposed in 2013 but did not have foundations on the good management of public space and the revitalization of something already existing without eradicating it, together with strategies that—from the architectural perception—do not keep the sector culturally active. That’s why, with the analysis of the dynamic and static relationships of the city, a great opportunity is developed to consolidate this sector of the race 16 through a cultural playful axis that lends itself to articulate the urban network, complemented by three zones for the revitalization of public space and the strengthening of the Huila culture.